Relationship between Sowing Time, Variety, and Quality in Safflower - Mehmet Oz (Journal of Chemistry)
This research was carried out to determine the rates of protein and oil production and fatty acid composition and their correlation coefficients in four safflower cultivars (Remzibey, Dincer, Balci, and Yenice) sown in the autumn and spring from 2013 to 2015. The experiment was carried out using split plots in a randomized block design and was replicated 3 times. The study found protein production rates between 15.20 and 18.08%, oil production rates between 24.58 and 31.99%, palmitic acid production rates between 5.93 and 7.01%, stearic acid production rates between 2.13 and 2.53%, oleic acid production rates between 12.08 and 31.58%, linoleic acid production rates between 78.61 and 59.08%, and linolenic acid production rates between 0.11 and 0.15%. Higher seed oil content values were obtained from spring sowing compared to autumn sowing (27.42% and 26.10%), and, in terms of both the evaluated sowing times and cultivars, the highest oil production rates were found in the Balci cultivar (32.20% and 31.78%) for both sowing times. It was determined that there is a positive and significant (r=0.476⁎⁎) relationship between oil with protein production rates but a negative and significant relationship between oil and linolenic acid production rates (r=-0.728⁎⁎). The oleic acid production rate was strongly negatively and significantly correlated with the linoleic acid production rate (r=-0.997⁎⁎).